Child Playing Online Game in the Sadd al-Zari'ah's Perspective - Muhammad Kurtubi (Nusantara: Journal of Law Studies, 2022)
Abstract: This study aims to find the sadd al-zari'ah review of children playing online games. This research is qualitative, and the approach taken is normative. The study results show that from the Perspective of sadd al -zari'ah, online games have an impact when children play them continuously, including negligence in time, unruly, declining health, leaving obligations, and reduced interest in learning. Some of these impacts are prohibited, even included in the illegitimate category. Therefore, in terms of sadd al -zari'ah, because the mafsada that is caused is greater than a grave sin, playing games is an act that is forbidden, and parents may even be obliged to prohibit their children from playing. Even so, if children play online games that do not have an impact that causes mafsada, such as setting time and not leaving obligations, parents may not forbid children from playing because playing is the right of children and online games are games that have permissible laws to play. Keywords: Children, Online Games, Sadd al-Zariah